Current opinion about hepatocellular carcinoma <10 mm - Dong, Yi; Teufel, Andreas; Wang, Wen-Ping; Dietrich, Christoph F. (Digestion, 2021)
Background: Early detection of hepatocellular carcinoma (HCC) is important. Advances in liver imaging techniques have facilitated the detection of HCC at an early stage. However, there is a controversial discussion on how to diagnose very small HCC by imaging. The aim of the current review is to present current published data on HCC ≤10 mm and discuss on how to best diagnose and treat such lesions. Summary: It is still challenging, however, to accurately characterize HCC <10 mm. The accuracy of contrast-enhanced ultrasound may be critical for early treatment decisions for cancer patients, particularly when CECT and/or CEMRI are inconclusive. Key Messages: The characterization of focal liver lesions <10 mm is frequently delayed until a follow-up imaging procedure demonstrates growth or stability. A repetition of ultrasound examination after 3 months for new nodules <1 cm should be recommended.